HAMBATAN KOMUNIKASI INTERPERSONAL PESERTA DIDIK KELAS XI DI SMK NEGERI 6 PADANG - Rosneli, Rosneli (Bimbingan dan Konseling, 2014)
Â The background of this research is about obstruction of interpersonal communication for participant that cannot be handled with maximal, focusing, and the purpose of the research is to know: 1) Physic obstruction in interpersonal communication of participant. 2) Physichologis obstruction in interpersonal communication of participant. 3) Semantic obstruction in interpersonal communication of participant.This research is Qualitative Research. Key informant is 2 person and 6 person are adding informant. The data is collected toward interview, observation and documentation for teachersâ action at class to become good students. This data is examined with doing triangulation and membercheck, after that the data is analyzed using 3 steps: 1. Reduction of data, 2. Showing of data, 3. Getting conclusion.In briefly, the result of this research: 1) Physic obstruction in interpersonal communication of participant, from the result of interviem above that is known limitation of listen what is said by the teacher and friends, sometimes listen or not, 2) Physicologis obstruction in interpersonal communication of participant which is known obstruction to assumpt real communication and key informant in assumpting communication that is said by friends, sometimes least understand by the key informant, 3) Semantic obstruction in interpersonal communication of participant with communicating between personality and maybe participant is to get knowing and understanding more good about out world, something world, events, knowledge, experience and others.This research is recommended for participant to get communicate more good of